Prejudice against Homosexuals and Social Representations of Homosexuality of Catholic and Evangelic Seminarians - Pereira, Cicero (2011)
This study analyzes the relationship between prejudice against homosexuals and social representations about homosexuality. Participants were 374 theology students (167 catholic and 207 evangelic) who individually answered a questionnaire about beliefs and attitudes toward homosexuals. Results allowed to identify two forms of prejudice: Subtle and blatant. The subtle prejudice is related to biological and psychosocial representations about homosexuality and to the disbelief in an ethical and moral nature of homosexuality. The blatant prejudice is related with the disbelief in a biological and psychosocial nature as well as with ethical and moral representations about homosexuality. In the discussion it is argued that social representations about the nature of minority groups can form the basis of prejudice and discrimination.